Peripheral Blood Leukocyte Subpopulation Changes in Reaction to an Acute Psychosocial Stressor as Compared to an Active Placebo-Stressor in Healthy Young Males: Mediating Effects of Major Stress-Reactive Endocrine Parameters - Lisa-Marie Walther; Angelina Gideon; Christine Sauter; Marcel Leist; Petra H. Wirtz (Cells)
Psychosocial stress has been proposed to induce a redistribution of immune cells, but a comparison with an active placebo-psychosocial stress control condition is lacking so far. We investigated immune cell redistribution due to psychosocial stress compared to that resulting from an active placebo-psychosocial stress but otherwise identical control condition. Moreover, we tested for mediating effects of endocrine parameters and blood volume changes. The final study sample comprised 64 healthy young men who underwent either a psychosocial stress condition (Trier Social Stress Test; TSST; n = 38) or an active placebo-psychosocial stress control condition (PlacTSST; n = 26). Immune cell counts and hemoglobin, epinephrine, norepinephrine, ACTH, renin, and aldosterone levels, as well as those of saliva cortisol, were determined before and up to 30 min after the TSST/PlacTSST. The TSST induced greater increases in total leukocyte, monocyte, and lymphocyte levels as compared to the PlacTSST (p’s ≤ 0.001), but in not granulocyte counts. Neutrophil granulocyte counts increased in reaction to both the TSST and PlacTSST (p’s ≤ 0.001), while eosinophil and basophil granulocyte counts did not. The psychosocial stress-induced increases in immune cell counts from baseline to peak (i.e., +1 min after TSST cessation) were independently mediated by parallel increases in epinephrine (ab’s ≤ −0.43; 95% CIs [LLs ≤ −0.66; ULs ≤ −0.09]). Subsequent decreases in immune cell counts from +1 min to +10 min after psychosocial stress cessation were mediated by parallel epinephrine, renin, and blood volume decreases (ab’s ≥ 0.17; 95% CIs [LLs ≥ 0.02; ULs ≥ 0.35]). Our findings indicate that psychosocial stress specifically induces immune cell count increases in most leukocyte subpopulations that are not secondary to the physical or cognitive demands of the stress task. Increases in the number of circulating neutrophil granulocytes, however, are not psychosocial stress-specific and even occur in situations with a low probability of threat or harm. Our findings point to a major role of epinephrine in mediating stress-induced immune cell count increases and of epinephrine, renin, and blood volume changes in mediating subsequent immune cell count decreases from +1 min to +10 min after psychosocial stress cessation.